2018
DOI: 10.1371/journal.pone.0193357
|View full text |Cite
|
Sign up to set email alerts
|

"Letting myself go forward past wrongs": How regulatory modes affect self-forgiveness

Abstract: The present research addresses the question of whether regulatory-mode orientations affect self-forgiveness. We expected that people with a strong locomotion orientation would be more inclined to self-forgiveness because of their tendencies toward movement and change, which focus them on the future, whereas people with a strong assessment orientation would refrain from self-forgiveness due to their evaluative tendencies which focus them on the past. These hypotheses were supported by the results in four studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 54 publications
(79 reference statements)
2
25
0
2
Order By: Relevance
“…Similarly, we anticipate that a supervisor will exhibit more relationship‐oriented leadership when his or her past temporal focus is incongruent (rather than congruent) with the team's past temporal focus. Individuals with a strong past temporal focus often hold long‐lasting grudges and, thus, find it difficult to overcome personal disputes (Pierro, Pica, Giannini, Higgins, & Kruglanski, ; Zakay & Fleisig, ). Also, these individuals place a strong emphasis on existing relationships and they are rather conservative in building new social connections (Park et al, ; Zimbardo & Boyd, ), whereas less past‐focused individuals attach limited value to (and more easily forget about) their personal relationship histories (Holman & Zimbardo, ; Zimbardo & Boyd, ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Similarly, we anticipate that a supervisor will exhibit more relationship‐oriented leadership when his or her past temporal focus is incongruent (rather than congruent) with the team's past temporal focus. Individuals with a strong past temporal focus often hold long‐lasting grudges and, thus, find it difficult to overcome personal disputes (Pierro, Pica, Giannini, Higgins, & Kruglanski, ; Zakay & Fleisig, ). Also, these individuals place a strong emphasis on existing relationships and they are rather conservative in building new social connections (Park et al, ; Zimbardo & Boyd, ), whereas less past‐focused individuals attach limited value to (and more easily forget about) their personal relationship histories (Holman & Zimbardo, ; Zimbardo & Boyd, ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Evidence shows that the urge toward movement and change of high locomotors, and the urge of evaluating the quality of one's course of action of high assessors, leads them to predict, in different ways, several phenomena (Higgins et al, ; Kruglanski, Pierro, & Higgins, ; Pierro, Chernikova, Lo Destro, Higgins, & Kruglanski, ). For instance, locomotion has been found to be positively related to self‐forgiveness (Pierro, Pica, Giannini, Higgins, & Kruglanski, ), and negatively related to nostalgia (Pierro, Pica, Klein, Kruglanski, & Higgins, 2013), counterfactual thinking and regret after failure (Pierro et al, ), while the opposite pattern was found for assessment. Consistently, high locomotors (as opposed to high assessors) have a preference for multitasking, by easily changing their focus on one task to another, and to focus as sooner as possible on things to do by avoiding procrastination (Pica, Amato, Pierro, & Kruglanski, ; Pierro, Giacomantonio, Pica, Kruglanski, & Higgins, , ).…”
Section: Regulatory Mode Theorymentioning
confidence: 99%
“…1 Self-forgiveness is positively associated with self-esteem, life satisfaction, and well-being, but negatively associated with neuroticism, depression, anxiety, and hostility. [2][3][4][5][6] Forgiveness of self and others has also been associated with physical health benefits, 7,8 a stronger immune system, 9 and reduced cardiovascular reactivity. [10][11][12][13] Nevertheless, physicians find self-forgiveness particularly challenging, 14 so acceptable evidence-based self-forgiveness tools to improve physicians' well-being are needed.…”
Section: Introductionmentioning
confidence: 99%